Childhood full and under-vaccination in Nigeria, 2013. Issue 48 (19th November 2018) - McGavin, Zoe A.; Wagner, Abram L.; Carlson, Bradley F.; Power, Laura E.; Eboreime, Ejemai; Boulton, Matthew L.
Highlights: In 2013, households in Nigeria were enrolled in the Demographic and Health Survey. Among 5759 children 1 year of age, only 25.5% were fully vaccinated. In total, 47.9% were under-vaccinated, and 26.6% had not received any vaccinations. Childhood vaccination should be improved among all groups. Vaccine promotion can focus on low coverage groups like Muslims and northerners. Abstract: Background: Nigeria's government is challenged with vaccinating the world's third largest birth cohort within a culturally and socioeconomically diverse country. This study estimated full childhood immunization coverage in Nigeria and characterizes the association between vaccination status and urbanicity, region of residence, ethnicity, and other factors. Methods: In 2013, households throughout Nigeria were enrolled in the Demographic and Health Survey which included questions about vaccination. We defined full vaccination of a child as having received a single dose of bacillus Calmete-Guerin (BCG), one dose of measles-containing vaccine (MCV), three doses of diphtheria, pertussis, tetanus (DPT), and four doses of oral polio vaccine (OPV). Using a multinomial logistic regression model, full vaccination and under-vaccination versus non-vaccination was regressed onto various demographic and socioeconomic characteristics. Results: Among 5759 children 1 year of age, 25.5% were fully vaccinated, 47.9% were under-vaccinated, and 26.6% had not received any vaccinations. Children were more likely to be fully vaccinated if they belonged to wealthier families, resided in southern regions of the country, were Christian, belonged to the Igbo or Yoruba ethnic group, had mothers who made ≥5 antenatal care visits, delivered at an institution, or were more highly educated. Conclusions: Full vaccination among children in Nigeria is exceptionally low by global standards and certain groups, such as Muslims and individuals in northern regions who are higher risk of non- or under-vaccination should be targeted by vaccination programs. Providing a wide range of health care services for mothers and pregnant women could improve full vaccination of children.